Preparation and Evaluation of Pimecrolimus Nanoemulsion for Topical Delivery - Sara Abdullah Challoob; Nidhal Khazaal Maraie (Iraqi Journal of Pharmaceutical Sciences, 2025)
One of the innovative approaches to delivering drugs via topical route is nanoemulation (NE), which is easy to manufacture, stable over the long term, and has a potent solubilization property. Pimecrolimus is a low water soluble drug used to treat psoriasis, eczema, atopic dermatitis and vitiligo. This work describes the high-energy ultrasonication technique used to prepare pimecrolimus nanoemulsion. A pseudo-ternary phase diagram was created in order to determine the ideal ratios of oil-surfactant/co-surfactant mixture for the creation of nanoemulsions. Based on pimecrolimus’s solubility in various oils, surfactants, and co-surfactants, Tween 80 was chosen as a surfactant, ethanol as a co-surfactant, and benzyl alcohol as an oil phase .The work involved creating twelve NE formulas for optimization, and evaluated for thier droplet size, visual transparency, entrapment efficiency, zeta potential, physical stability, and in vitro release. Droplet size is 45.1 nm, entrapment efficiency is 92.59%, PDI is 0.402, Zeta potential is -0.8 mV, were displayed by the ideal NE formula, which released 76.3% in 5h and 96.6% of pimecrolimus in 24h compared with the commercial cream which released 26.2% in 5h and 42.5% of the drug in 24h. This suggests that the prepared formula has promising potential as an effective nanocarrier to enhance drug solubility and permeability and, consequently, its therapeutic effectiveness topically through the skin. These results demonstrated the formula’s promising potential as an effective nanocarrier to improve drug solubility and permeability and, consequently, its therapeutic effectiveness topically through the skin.